2013
DOI: 10.1177/1533317513494452
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Analysis of Mild Alzheimer’s Disease and Normal Aging Using Volume of Hippocampal Subfields and Hippocampal Mean Diffusivity

Abstract: Atrophy was present in almost all hippocampal subfields at mild AD stage. The volumes of CA1 and subiculum were of the most diagnostic significance in discrimination of mild AD, which can be improved by the combination of volume and diffusivity analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
44
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 42 publications
8
44
4
1
Order By: Relevance
“…In some studies, abnormalities were also found in medial regions of the surface, mostly corresponding to the (pre)subiculum (Frisoni et al, , 2006Wang et al, 2006) or even in all subfields Chow et al, 2012Chow et al, , 2015. Using direct volumetry in AD patients, several studies reported significant atrophy in all, or almost all, investigated subfields (Adachi et al, 2003;Boutet et al, 2014;de Flores et al, 2015;Khan et al, 2014;La Joie et al, 2013;Li et al, 2013), the major atrophy being generally located in CA1 (La Joie et al, 2013;de Flores et al, 2015;Mueller et al, 2010). In a few studies, some subfields were (relatively) spared, namely CA3/DG (Mueller and Weiner, 2009; or CA2 (Wisse et al, 2014b).…”
Section: Subfield Imaging In Admentioning
confidence: 96%
See 1 more Smart Citation
“…In some studies, abnormalities were also found in medial regions of the surface, mostly corresponding to the (pre)subiculum (Frisoni et al, , 2006Wang et al, 2006) or even in all subfields Chow et al, 2012Chow et al, , 2015. Using direct volumetry in AD patients, several studies reported significant atrophy in all, or almost all, investigated subfields (Adachi et al, 2003;Boutet et al, 2014;de Flores et al, 2015;Khan et al, 2014;La Joie et al, 2013;Li et al, 2013), the major atrophy being generally located in CA1 (La Joie et al, 2013;de Flores et al, 2015;Mueller et al, 2010). In a few studies, some subfields were (relatively) spared, namely CA3/DG (Mueller and Weiner, 2009; or CA2 (Wisse et al, 2014b).…”
Section: Subfield Imaging In Admentioning
confidence: 96%
“…Thus, all FreeSurfer 5.3 studies have detected volume loss in the subiculum and the CA2/3 region in MCI and AD patients, while only a few articles(Khan et al, 2014;Li et al, 2013) also reported CA1 atrophy (SeeTable 1, bottom section). As mentioned above, this might be due to difference in subfield definition and boundaries used in FreeSurfer 5.3.…”
mentioning
confidence: 94%
“…However, none of these studies assessed the relationship between microstructural damage in the hippocampus and memory performance in aMCI. Numerous studies have also demonstrated that the hippocampal subfields are differentially affected by pathological damage, and DTI parameters may be more sensitive and quantifi able measures of early degeneration in AD than conventional MR imaging techniques [44] .…”
Section: Patientsmentioning
confidence: 99%
“…The silent period, if properly detected, would permit the administration of therapies geared to curbing disease progression before the magnitude of nerve tissue damage is too extensive. One of the most commonly used markers to verify disease progression is neuroimaging examination of the hippocampal formation to detect early atrophy in this region (3,5,8,16,20,23,54,63).…”
Section: Introductionmentioning
confidence: 99%